Performance analysis of ISO Management System Standards certification Consulting Firms of Pakistan - Muhammad Bilal Mirza; Nawar Khan (EQA, 2023)
International Standards of Organization (ISO) management system standards certification (IMS) is the most common standard way to benefit the companies that decided to use it. The reason for this research is to analyze the performance of IMS consulting firms in Pakistan and the initiatives taken by the Government of Pakistan (GoP) in the implementation of IMS in the organizations with a moderating role of International Register of Certificated Auditors (IRCA) to maintain quality of products and services in Pakistan. A positivist examination worldview with expressive cross-sectional exploration configuration was chosen to gather essential information from the top-level management, the middle-level, and the low-level employees of ISO-certified firms and team members working in ISO consultancy firms. The data was collected from different cities using an online survey, skype, and telephone because of COVID-19 restrictions. The findings of this study are that there are a total of 31 ISO-certified consulting firms/certification bodies working in Pakistan. Only eight of these are registered with Pakistan National Accreditation Council (PNAC) whereas the remaining are unregistered. The reason identified for the lesser amount of ISO certification in Pakistan is the lack of interest from the GOP. It is because they are not providing any incentive programs to IMS consulting firms.